Tartu–Moscow school of semiotics and history - Boyko, Taras (Historein, 2014)
The article examines and contextualises a corpus of ideas by members of the Tartu–Moscow (semiotic) school, which was dedicated to various issues connected with theoretical aspects of history, historiography, the historian’s craft, and the nature of historical research per se.